Tomato quality as influenced by different packaging materials and practices - Zewdie, Tsegahun Mekonnen (Journal of Scientific Agriculture, 2017)
In this study, the effect of retailing packaging material on tomato quality was investigated. Specifically, non-defective tomato fruits were selected after harvest and packed in four different packaging materials; open market bag, open box, sealed box and Xtend bag. A total of six treatments were prepared by storing the packaged fruits at 4 or 17°C for 10 days. Quality attributes of tomatoes such as calyx freshness, weight loss, fruit firmness, total soluble solids (TSS), colour and physiological damage were assessed. Generally, both packaging material and storage temperature affected the quality of the tomato fruits. The quality of tomato fruits stored at 4oC was generally superior to those stored at 17°C.Calyx of tomato fruits stored in open market bag (stored at 17°C) and open box (stored at 17°C) were very dry after storage compared to the tomato fruits stored at 4°C. Tomato fruits packed in Xtend bag and sealed box were firmer than those packed in open box and open market bag. The carbon dioxide (CO2) concentration in sealed box was substantially higher (8.25%) than that in Xtend bag (2.07%). In contrast, the oxygen (O2) concentration in the Xtend bag was higher (18.90%) than that in the sealed box (14.75%). Tomatoes packed in Xtend bag and sealed box had minimal changes in colour intensity (C*), showed lower TSS values compared to tomato fruits packed in other packaging materials. Xtend bag and sealed box seems to be better packaging material for storing tomato fruits for a period of 10 days.